Effects of atorvastatin on endothelial function and the expression of proinflammatory cytokines and adhesion molecules in young subjects with successfully repaired coarctation of aorta. Issue 4 (10th November 2011) - Brili, S; Tousoulis, D; Antonopoulos, A S; Antoniades, C; Hatzis, G; Bakogiannis, C; Papageorgiou, N; Stefanadis, C
Abstract : Objective: To investigate the effects of atorvastatin on endothelial function and low-grade systemic inflammation in subjects with successful surgery for aortic coarctation repair (SCR). Design: Open-label study. Setting: Outpatients visiting the adult congenital heart disease department of our hospital. Patients: 34 young people with SCR. Interventions: Patients with SCR received atorvastatin 10 mg/day (n=17) or no treatment (n=17) for 4 weeks. At baseline and at 4 weeks, endothelial function was assessed by flow-mediated dilatation (FMD) of the right brachial artery, and blood samples were obtained. Serum levels of interleukin (IL) 1b, IL-6 and soluble vascular cell adhesion molecule-1 (sVCAM-1) were determined by ELISA. Main outcome measures: Effects of treatment on FMD and serum levels of IL-1b, IL-6 and sVCAM-1. Results: FMD in the atorvastatin group was significantly improved after 4 weeks (from 6.46±0.95% to 11.24±1.38%, p<0.01), while remaining unchanged in the control group (from 6.74±0.58% to 6.95±0.53%, p=NS). Even though atorvastatin had no effect on serum IL-6 levels (0.62 (0.37–0.88) pg/ml to 0.53 (0.28–0.73) pg/ml, p=NS), it significantly reduced circulating levels of IL-1b (from 1.17 (0.92–1.77) pg/ml to 1.02 (0.75–1.55) pg/ml, p<0.05) and sVCAM-1 (from 883.4 (660.3–1093.1) ng/ml to 801.4 (566.7–1030.2) ng/ml, p<0.05). No changes were seen in serum levels of IL-6, IL-1b and sVCAM-1 in the control group after 4 weeks compared with baseline (p=NS for all). Conclusions: Atorvastatin treatment for 4 weeks in subjects with SCR significantly improved endothelial function and suppressed systemic inflammatory status by decreasing circulating levels of IL-1b and sVCAM-1.